Transforming the Digital Ecosystem of Islamic Boarding Schools: Evidence from Ash-Shiddiiqi Islamic Boarding School, Muaro Jambi - Suci Fitriani; Mukhtar Mukhtar; Muhamad Taridi (UMSU, 2026)
Digital transformation has become a strategic imperative for educational institutions, including Islamic boarding schools, in responding to the challenges and competition of the digital era. This study aims to analyze the transformation of the digital ecosystem and its role in enhancing competitive advantage in Khalafiah Islamic boarding schools through a case study of Ash-Shiddiiqi Islamic Boarding School in Muaro Jambi. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis involving pesantren leaders, teachers, and students. The data were analyzed using thematic analysis. The findings reveal that digital ecosystem transformation at Ash-Shiddiiqi Islamic Boarding School involves the implementation of iPad-based learning, the staged development of students’ digital literacy, the utilization of digital media for institutional communication and branding, and digital governance supported by strong leadership. This transformation not only improves learning quality and institutional capacity but also enhances transparency, stakeholder engagement, and institutional competitiveness. The study concludes that a well-structured digital ecosystem constitutes a new and powerful source of competitive advantage for Khalafiah Islamic boarding schools when aligned with institutional values and governance.